ANALISIS PENGARUH STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN DI TOA BAJA KITCHEN & COFFEE CIREBON - Celine Celine; Roels Ni Made Sri Puspadewi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Toa Baja Kitchen & Coffee as a restaurant in the Cirebon area, is able to attract many customers on weekdays and holidays. With so many customers coming, it will raise the question